2022
DOI: 10.1021/acsomega.1c07395
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Phospholipid and a Coagulating Protein: Potential Candidate for Bioelectronic Applications

Abstract: In the present communication, we have investigated the interaction between a biomembrane component 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) and a coagulating protein protamine sulfate (PS) using the Langmuir–Blodgett (LB) technique. The π– A isotherm, π– t characteristics, and analysis of isotherm curves suggested that PS strongly interacted with DOPC, affecting the fluidity of the DOPC layer. Electrical characterization indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
1
2
0
1
Order By: Relevance
“…A comparison with the previously reported results (Table ) suggests that for biomaterial-based WORM devices, the threshold voltage observed in the present case is lower, which is advantageous in terms of lower power consumption …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…A comparison with the previously reported results (Table ) suggests that for biomaterial-based WORM devices, the threshold voltage observed in the present case is lower, which is advantageous in terms of lower power consumption …”
Section: Resultssupporting
confidence: 78%
“…A comparison with the previously reported results (Table 1) suggests that for biomaterial-based WORM devices, the threshold voltage observed in the present case is lower, which is advantageous in terms of lower power consumption. 41 The device yield, that is, device reproducibility, has also been investigated for the Au/Lyso/ITO device for both the initial sweep directions. In order to do this, 84 independent switchable devices in two ITO-coated glass slides (7 × 6 arrays) have been prepared.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been observed that both the devices can retain their ON state after switching even up to 1000 consecutive scan cycles (0→2→0→2). Such resistive switching has a lot of applications in molecular electronics especially towards designing write once read many memory applications (WORM) [42,44]. Threshold voltage for complex 1 based device was VTH1 = 1.16 V and that for complex 4 based device was VTH4 = 1.53 V. The observed difference in threshold voltages may be due to difference in structure of the two complexes as well as their organization within the device active layer.…”
Section: Resultsmentioning
confidence: 99%
“…LB 膜,包括纳米颗粒,高分子聚合物 [72][73] ,蛋白质 和生物分子 [74][75] 。Chen 等 [59] [76][77] 在无机压电陶瓷表面,通过 活性表面官能团形成界面键,提高了填料和聚合物 基体之间的界面连接和锚定强度,提高了重复外部 冲击下的耐久性和拉伸性。 Su 等 [60] 将多巴胺包覆的…”
Section: 柔性压电材料的制备unclassified